2011
DOI: 10.1080/02701367.2011.10599780
|View full text |Cite
|
Sign up to set email alerts
|

Self-Controlled Amount of Practice Benefits Learning of a Motor Skill

Abstract: Self-control over factors involving task-related information (e.g, feedback) can enhance motor learning. It is unknown if these benefits extend to manipulations that do not directly affect such information. The purpose of this study was to determine if self-control over the amount of practice would also facilitate learning Participants learned to throw a dart using their nonpreferred hand. The self-control (SC) group decided when to stop practice. The yoked group completed the same number of trials as their SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(24 citation statements)
references
References 23 publications
1
21
0
2
Order By: Relevance
“…Self-control (SC) manipulations have been shown to facilitate learning for a variety of tasks, including those that require sequence learning (Chen et al, 2002; Chiviacowsky and Wulf, 2002, 2005; Patterson and Carter, 2010) and object projection (Janelle et al, 1995, 1997; Chiviacowsky et al, 2008; Kolovelonis et al, 2010). Types of previously examined SC manipulations have included physical guidance (Wulf and Toole, 1999; Wulf et al, 2001), amount of practice (Post et al, 2011), task scheduling (Keetch and Lee, 2007; Wu and Magill, 2011), video demonstration (Wrisberg and Pein, 2002; Wulf et al, 2005), and augmented feedback (Janelle et al, 1995; Chiviacowsky et al, 2008). The majority of these studies have examined the effects of SC feedback in the form of knowledge of results (KR) or, less frequently, knowledge of performance (KP).…”
Section: Introductionmentioning
confidence: 99%
“…Self-control (SC) manipulations have been shown to facilitate learning for a variety of tasks, including those that require sequence learning (Chen et al, 2002; Chiviacowsky and Wulf, 2002, 2005; Patterson and Carter, 2010) and object projection (Janelle et al, 1995, 1997; Chiviacowsky et al, 2008; Kolovelonis et al, 2010). Types of previously examined SC manipulations have included physical guidance (Wulf and Toole, 1999; Wulf et al, 2001), amount of practice (Post et al, 2011), task scheduling (Keetch and Lee, 2007; Wu and Magill, 2011), video demonstration (Wrisberg and Pein, 2002; Wulf et al, 2005), and augmented feedback (Janelle et al, 1995; Chiviacowsky et al, 2008). The majority of these studies have examined the effects of SC feedback in the form of knowledge of results (KR) or, less frequently, knowledge of performance (KP).…”
Section: Introductionmentioning
confidence: 99%
“…Autonomy support, or conditions that are supportive of individuals' need for control or autonomy in their actions, are important for motivation, performance, and learning (e.g., Deci & Ryan, 2008;Cordova & Lepper, 1996;Tafarodi, Milne, & Smith, 1999). In the motor learning literature, many studies have demonstrated that learning is enhanced when learners have the opportunity to make decisions about aspects of practice conditions, including the delivery of feedback, skill demonstrations, or amount of practice (e.g., Janelle, Barba, Frehlich, Tennant, & Cauraugh, 1997;Post, Fairbrother, & Barros, 2011;Wulf, Raupach, & Pfeiffer, 2005; for a recent review, see Wulf & Lewthwaite, 2016). There is also increasing evidence that providing even small or incidental choices that do not have direct task relevance can be sufficient to enhance motor performance or learning.…”
mentioning
confidence: 99%
“…Self-controlled training provides the participant with control over their own learning, during the practice session, leading to a more active role and increased motivation; as well as a tailored practice experience to meet their individual needs (Chiviacowsky et al, 2008;Post, Fairbrother & Barros, 2011). The highly structured and instructor-controlled KM training protocol may have been beneficial when first learning the skills, however, as participants in the MT group continued training throughout the study, it is possible that they felt "forced" into a given practice schedule and volume of practice prescribed by the highly contrived experiment-based context for training.…”
Section: Measurementioning
confidence: 99%